"All‐in‐One" Nanoparticles for Trimodality Imaging‐Guided Intracellular Photo‐magnetic Hyperthermia Therapy under Intravenous Administration. (8th January 2018) - Yan, Hao; Shang, Wenting; Sun, Xiaodan; Zhao, Lingyun; Wang, Jingyun; Xiong, Zhiyuan; Yuan, Jie; Zhang, Ranran; Huang, Qianli; Wang, Kun; Li, Baohua; Tian, Jie; et al.
Abstract: Great efforts have been devoted so far to combine nano‐magnetic hyperthermia and nano‐photothermal therapy to achieve encouraging additive therapeutic performance in vitro and in vivo with limitation to direct intratumoral injection and no guidance of multimodality molecular imaging. In this study, a novel multifunctional theranostic nanoplatform (MNP@PES‐Cy7/2‐DG) consisting of magnetic nanoparticles (MNPs), poly(3, 4‐ethylenedioxythiophene):poly(4‐styrenesulfonate) (PES), Cyanine7 (Cy7), and 2‐deoxyglucose (2‐DG)‐polyethylene glycol is developed. They are then applied to combined photo‐magnetic hyperthermia therapy under intravenous administration that is simultaneously guided by trimodality molecular imaging. Remarkably, nanoparticles are found aggregated mainly in the cytoplasm of tumor cells in vitro and in vivo, and exhibit stealth‐like behavior with a long second‐phase blood circulation half‐life of 20.38 ± 4.18 h. Under the guidance of photoacoustic/near‐infrared fluorescence/magnetic resonance trimodality imaging, tumors can be completely eliminated under intracellular photo‐magnetic hyperthermia therapy with additive therapeutic effect due to precise hyperthermia. This study may promote a further exploration of such a platform for clinical applications. Abstract : A novel multifunctional theranostic nanoplatform (MNP@PES‐Cy7/2‐DG) is developed and applied for combined photo‐magnetic hyperthermia therapy under intravenous administration, which is simultaneously guided by multimodality molecular imaging. Under the guidance of photoacoustic imaging/magnetic resonance imaging/fluorescence molecular imaging tumors can be completely eliminated under intracellular inside‐out hyperthermia with additive therapeutic effect due to precise hyperthermia.